2010
DOI: 10.1590/s1982-56762010000400009
|View full text |Cite
|
Sign up to set email alerts
|

Infecção de sementes de trigo com Bipolaris sorokiniana pela técnica de restrição hídrica

Abstract: RESUMOA inoculação de fungos fitopatogênicos em sementes pela técnica da restrição hídrica é relativamente recente. Este trabalho objetivou avaliar o efeito de potenciais osmóticos (-0.4, -0,6 e -0.8) do substrato BDA, modificado por adição de sacarose, em interação com o tempo de exposição (46, 72 e 96 h), na infeção de sementes de trigo por Bipolaris sorokiniana. Foram analisadas a eficiência da infecção e a inibição da germinação durante e após a aplicação dos tratamentos. De acordo com os resultados, perío… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
2
2
0
1
Order By: Relevance
“…Similar results were observed in cotton, rice, sunflower, and common bean seeds [53,56,57]. Several studies reported that the incubation period to obtain inoculated seeds ranged between 24 and 144 h [58,59,60,61].…”
Section: Discussionsupporting
confidence: 76%
“…Similar results were observed in cotton, rice, sunflower, and common bean seeds [53,56,57]. Several studies reported that the incubation period to obtain inoculated seeds ranged between 24 and 144 h [58,59,60,61].…”
Section: Discussionsupporting
confidence: 76%
“…In short, 24 hours proved to be long enough for P. tritici-repentis infection, penetrating easily through the protective tissues of wheat seeds. Farias et al (2010) found similar results studying wheat seeds at different water potentials and inoculation times, noting that infection by B. sorokiniana was induced with an average efficiency of 53 to 92%. Several other studies have shown that infection efficiency depends on the pathogen species.…”
Section: Exposure Time Of Wheat Seeds To P Tritici-repentis At Diffesupporting
confidence: 68%
“…Water stress is used to control or inhibit seed germination under different circumstances such as in health tests on paper substrate (CELANO et al, 2012) and potato dextrose agar medium (PDA) (GARCIA JÚNIOR et al, 2008), and in fungal inoculation tests (FARIAS et al, 2010), besides simulating water deficit (GIROTTO et al, 2012), osmotic and matric conditioning (QUEIROGA et al, 2011) for crops of interest. A water restriction condition can be obtained by adjusting water potential with osmotically active solutes, with the most common being mannitol, polyethylene glycol, maltose (GIROTTO et al, 2012), KCl, NaCl, sucrose (GARCIA JÚNIOR et al, 2008), or CaCl 2 (MACHADO NETO et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Lotes contaminados nem sempre estão disponíveis prontamente ou contém o tipo de patógeno e os níveis desejados de infecção, dificultando os estudos no âmbito da patologia de sementes (FARIAS et al, 2010). Contudo, com a modificação do potencial osmótico do substrato, técnica esta denominada restrição hídrica (COUTINHO et al, 2001;MACHADO;LANGERAK, 2002;MACHADO et al, 2008) é possível promover diferentes níveis de infecção por fungos nas sementes, além de inibir a germinação das mesmas (MACHADO et al, 2004, ARAUJO et al, 2006.…”
Section: Introductionunclassified